Organization of Prison System in Serbia - Stevanović, Zoran M. (Zbornik Instituta za kriminološka i sociološka istraživanja, 2012)
The organisation and internal functioning of the prison system in Serbia, the jurisdiction over the execution of criminal sanctions and the prison system, as well as the problems that appear in the working of prisons, are reviewed in this paper. The structure of the prison system in Serbia is comprised of two components: Penitentiary Institutions and Central Administration at the Director’s Headquarters. Penitentiary Institutions are intended for the execution of prison sentences, juvenile prison sentences, security measures of compulsory psychiatric treatment and confinement in a medical institution, compulsory alcohol addiction treatment, compulsory drug addiction treatment, for the execution of educational measures of remand to a correctional institution, as well as for the execution of the measure of detention. In Serbia, there are 28 penitentiary institutions of different types and categories. In the Headquarters of the Direction, 6 departments, which are defined according to the type of work and jurisdiction, and 1 Centre for the Education of Employees, have been established. The prison system represents a complex organisation, which, under current conditions, shows a significant amount of problems that appear as the consequences of: overcrowded prisons, inefficient organisation and management, inadequate professional education of prison staff, unsatisfactory financial position, unsolved social status, etc.